Major salivary gland agenesis in a young child: consequences for oral health - N. HEATH, I. MACLEOD, & R. PEARCE (Paediatric Dentistry, 2006)
Salivary gland agenesis is a rare condition. It can be associated with some equally rare syndromes so that diagnosis can be delayed.